Intracardiac contrast echoes during transvenous His bundle ablation. Issue 3 (March 1985) - Rowland, E; Foale, R; Nihoyannopoulos, P; Perelman, M; Krikler, D M
Abstract : Two patients undergoing endocavitary ablation for resistant supraventricular tachycardia had cross sectional echocardiography performed during the ablative procedure. In both cases immediate opacification of the right heart cavities occurred at the time of the current discharge. The contrast effect was similar to that resulting from a peripheral venous injection of dextrose or saline during echocardiography for the diagnosis of intracardiac shunts. In one patient contrast echoes were also seen in the left ventricle. This contrast effect may be produced by gaseous release or blood element destruction. The risk of embolisation in patients undergoing endocavitary ablation, particularly on the left side of the heart, should be further evaluated.